Field reports, Iowa Bird Life, Lee Schoenewe, spring 1999 - Schoenewe, Lee A.et al (1999)
An annotated list of birds sighted by Lee Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed